Getir Kehidupan Idola di Jepang dalam Trilogi “Sarishinohara” Karya Mikito-P - Barokah, Ismawati; Ridha, Dian Annisa Nur (Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
This research examines the representation of idol life in Mikito-P’s “Sarishinohara” song trilogy whose titles consist of “Sarishinohara”, “Yonjuunana”, and “Akaito” using the Roland Barthes semiotic model theory. The purpose of this study is to determine the physical structure and inner structure of the song lyrics of the “Sarishinohara” trilogy, then analyze the denotation, connotation, and myth contained in the music video according to the Roland Barthes semiotic model. The research method uses qualitative research methods or is written in descriptive form. Based on the results of data analysis, it is known that the negative side of idol life in Japan is in the form of mental pressure experienced by idols, limitations in relationships, and negative public behavior towards idols